2012
DOI: 10.1177/1073858411431646
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the BDNF Val66Met Polymorphism on Cognition

Abstract: Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophin growth factor family and is implicated as a modulator of neuronal survival and differentiation, synaptic plasticity, and higher order cognitive functions such as learning and memory. A common single-nucleotide polymorphism (SNP) has been identified in the human BDNF gene (BDNF Val66Met) that leads to decreased BDNF secretion and impairments in specific forms of learning in humans. To better understand the impact of this SNP on biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 55 publications
5
85
0
1
Order By: Relevance
“…Next, we evaluated the occurrence of this window of epigenetic plasticity also in the humanized mouse model of BDNF loss-of-function (BDNFVal66Met). The Val66Met SNP is carried by 33% of the human population and has been associated with the development of neuropsychiatric disorders (21,22). Here, we found that a subset of naive heterozygous BDNFVal66Met mice, identified at the light-dark screening method as particularly anxiety-prone (2) (Fig.…”
Section: P300 Regulates the Mglu2-driven Window Of Plasticity Opened mentioning
confidence: 73%
See 1 more Smart Citation
“…Next, we evaluated the occurrence of this window of epigenetic plasticity also in the humanized mouse model of BDNF loss-of-function (BDNFVal66Met). The Val66Met SNP is carried by 33% of the human population and has been associated with the development of neuropsychiatric disorders (21,22). Here, we found that a subset of naive heterozygous BDNFVal66Met mice, identified at the light-dark screening method as particularly anxiety-prone (2) (Fig.…”
Section: P300 Regulates the Mglu2-driven Window Of Plasticity Opened mentioning
confidence: 73%
“…From a translational standpoint, BDNF signaling is also relevant. For example, 33% of the human population present a BDNF Val66Met SNP that leads to a valine-to-methionine substitution in the BDNF protein at codon 66, and this SNP has been associated with increased susceptibility to development of stress-related disorders (21,22). …”
mentioning
confidence: 99%
“…A growing body of evidence demonstrates that BDNF is involved in the pathophysiology and treatment of depression as well as in learning and memory (Dincheva et al 2012;Krishnan and Nestler 2008). Clinical data showed that in individuals with depression, BDNF was reduced in the hippocampus, and antidepressant treatment normalized the BDNF expression (Autry and Monteggia 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Since being established as a functional variant, the Val66Met polymorphism has been implicated as a modifier of neurocognitive function. 5 Memory performance was the first cognitive domain to be extensively screened for the effects of the Val66Met polymorphism, and while several types of memory impairments have been associated with the mutant 66Met allele in both humans 5 and mice, 20,39 episodic memory 3,40,41 has been shown to be particularly affected by restricted activity-dependent secretion of BDNF. Translating cognitive performance to brain structure and function, the effects of the Val66Met on hippocampal function and morphology has been the topic of much investigation.…”
Section: Human Neuroscience Of the Val66met Polymorphismmentioning
confidence: 99%
“…3 Genetic association studies have shown that the Val66Met polymorphism may be a risk factor for the development of neuropsychiatric disorders, 4 and that there is evidence that the polymorphism modulates aspects of neurocognitive function in otherwise healthy adults. 5 Since 2003, the year in which the Val66Met polymorphism was first described as a functional variant, 3 the number of studies evaluating the effects of this evolutionarily recent genetic aberration has progressively increased ( Figure 1). The pace of publication on BDNF and the Val66Met polymorphism has produced a gap in knowledge integration both between and within fields interested in the functional effects of this variant and the trophic effects of BDNF in its wild-type form.…”
Section: Introductionmentioning
confidence: 99%